Evaluation of Direct Cash Assistance Policy in Minaesa Village, Wori District, North Minahasa Regency - Bugis, Gifari; Sendouw, Recky; Steven V. Tarore, (Technium Social Sciences Journal, 2024)
This research aims to evaluate the Direct Cash Assistance (BLT) distribution policy in Minaesa Village, Wori District, North Minahasa Regency. The type of research used is qualitative. The data sources used include primary and secondary data obtained through observation, interviews, and documentation. The collected data is classified based on type and form and then presented descriptively. After that, all data were analyzed and discussed in detail, followed by conclusions as a result of this research. The results of the research show that overall BLT distribution in Minaesa Village, Wori District, North Minahasa Regency, was successful in achieving the target and some were not. Evaluation of this Policy is based on indicators of effectiveness and adequacy, which have generally worked as expected. However, there is a lack of transparency in the announcement of potential BLT recipients by the Minaesa Village government, which does not cover all points that are easily accessible to the village community. Apart from that, the accuracy indicator shows that not all people who are entitled to receive BLT get it, because some of them do not meet the requirements or are eliminated due to the distribution of regional quotas.